Qualitative assessment of hand hygiene knowledge, attitudes and practices among healthcare workers prior to the implementation of the WHO Hand Hygiene Improvement Strategy at Faranah Regional Hospital, Guinea - Moussa Douno; Carlos Rocha; Matthias Borchert; Ibrahima Nabe; Sophie Alice Müller (PLOS Global Public Health, 2023)
Healthcare-associated infections are a serious burden globally. Few qualitative studies have explored healthcare workers’ knowledge, attitudes and practices of hand hygiene. Prior to the implementation of the World Health Organization’s Hand Hygiene Improvement Strategy at Faranah Regional Hospital in the Upper Region of Guinea in December 2018, we conducted a qualitative baseline assessment of knowledge, attitudes and practices of hand hygiene among healthcare workers to guide future hand hygiene interventions. The qualitative study consisted of direct observations, In-Depth Interviews (IDIs) and Focus Group Discussions (FGDs). We found that the 2013–16 Ebola outbreak had had a pivotal impact on healthcare workers’ knowledge, attitudes and practices. The severity of the disease and the training provided for infection control were responsible for their knowledge acquisition and adoption of good attitudes and practices. However, negligence, resulting in poor hand hygiene practices, rose after the outbreak, once the “cue of fear” that had motivated workers for their own self-protection had waned. Our results suggest that local capacity building through training and availability of hand hygiene materials would be a sustainable approach to enhance hand hygiene culture at the hospital. Our study suggests that there is a need for a high and long-term commitment of authorities and healthcare workers at all levels for a sustainable hand hygiene culture.